CARRYING CAPACITY AND FEEDING PREFERENCES OF SUMATRAN ELEPHANTS (Elephas mazimus Sumatranus) IN THE ISAU-ISAU FOREST GROUP, LAHAT DISTRICT, SOUTH SUMATRA PROVINCE - Rosianty, Yuli; Lensari, S.Hut, M.Si, Delfy; Wiranata, Aldi (Universitas Muhammadiyah Palembang, 2024)
The habitat of the Sumatran Elephant (Elephas maximus Sumatranus) can be found in several types of forest, where naturally elephants need a large area to forage for food and spend time in primary (protected) forest during the day and out into open forest (secondary forest) during hot times. the sun has diminished. Elephants also need a safe and comfortable atmosphere so that their mating behavior (breeding) is not disturbed and their reproductive process can run well. This makes elephants very dependent on natural habitats to breed and find food. This research aims to find out what types of food preferences elephants have and the distribution of elephant food in the Natural Reserve Forest Area of the Isau-Isau Forest Group Elephant Training Center during ± 2 (two) Months. The method used in the research is descriptive qualitative and quantitative research. Results of research on the types of vegetation that Sumatran elephants (Elephas maximus Sumatranus) feed on in the HSA PLG KH Isau-Isau area, West Merapi District, Lahat Regency, South Sumatra Province in July 2023. This observation was carried out on all Sumatran elephants (Elephas maximus Sumatranus) found in HSA PLG KH Isau-Isau, West Merapi District, Lahat Regency, South Sumatra Province. From data obtained in the field in the HSA PLG KH Isau-Isau area, West Merapi District, Lahat Regency, South Sumatra Province, there are 8 Sumatran elephants (Elephas maximus Sumatranus) with 1 male elephant and 7 female elephants. From data in the field there are 16 The type of food for elephants at the observation location with the favorite food for all elephants is Belidang (Fimbristylis annua) with a long eating time with an average of 3.1 minutes to eat for 15 minutes and a food preference index of 0.226, while for plants the most Elephants quickly eat the Lentahi plant (Molineria capitulate) with a feeding time of 1 minute with a Feeding Preference Index of 0.067.